2021
DOI: 10.2166/ws.2021.346
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sustainability index for rural water management using ANN

Abstract: The current study proposes a sustainability index (SI) measure based on artificial neural networks (ANN) and globally accepted parameters. Some of the available methods for SI measurement are multi-criteria analysis, external costs, energy analysis, and ecological footprint methods. However, validity remains a concern due to a system's needs, criteria, and requirements. Generally, sustainability is assessed in economic, environmental, and social issues, which varies across regions and countries. Most of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…A risk assessment model for infrastructure projects was developed by [38] using a BP-ANN algorithm. The sustainability index for water management was assessed with the utilization of an ANN [39]. A hybrid ANN was developed by [40] to evaluate the sustainability of construction projects.…”
Section: Rehabilitation Selection Methodsmentioning
confidence: 99%
“…A risk assessment model for infrastructure projects was developed by [38] using a BP-ANN algorithm. The sustainability index for water management was assessed with the utilization of an ANN [39]. A hybrid ANN was developed by [40] to evaluate the sustainability of construction projects.…”
Section: Rehabilitation Selection Methodsmentioning
confidence: 99%
“…Publications demonstrated that the "sustainability index" had diverse applications and contexts in which it was used. Some publications focused on water resource planning and management [50], water and wastewater management [57], the responsible use of water by companies [58], rural water management [59], offshore wind farms and aquaculture [60], integrated water resource management [61], and specific river watersheds [62]. Each publication focused on applying a sustainability index within its specific domain.…”
Section: Six Clusters Of Water Sustainability Indicesmentioning
confidence: 99%
“…The publications aimed to evaluate and assess sustainability within their respective contexts. Some publications sought to extend or refine the definition of the sustainability indexes [50], evaluate the sustainability of specific sectors or practices [57,59,60], or assess the impacts of climate change on integrated water resource management [61]. The publications employed different methodologies to develop and assess the sustainability indexes.…”
Section: Six Clusters Of Water Sustainability Indicesmentioning
confidence: 99%
See 1 more Smart Citation